French CEO compensations: what is the cost of a mandatory upper limit? - Fabienne Llense (Center for Economic Studies and ifo Institute (CESifo), 2008)
In the middle of the nineties, the sharp increase in globalisation and the last privatization wave have promoted the shaping of a market for executives in France. Characteristics of this market are estimated for France and a competitive model is simulated in order to assess to what extend such a model could explain the observed CEO compensations. The size elasticity of compensation in France is equal to 0.5 and justifies a large magnitude in compensation. To moderate those compensations, a wage cap is often called for by opinion and the European left but also, more surprisingly, by representative of shareholders. The cost of this policy is evaluated in this sorting model and the lobbying of shareholders is explained.
Keywords: J31; J33; D33; D41; 330; Führungskräfte; Gehalt; Vergütungssystem; Regulierung; Wirtschaftspolitische Wirkungsanalyse; Führungskräfteauswahl; Matching; Betriebsgröße; Theorie; Frankreich